PEMANFAATAN KONTEN DIGITAL PUSAT SUMBER BELAJAR (PSB) PADA SEKOLAH RINTISAN PENERIMA BANTUAN PERANGKAT PSB - Eni Susilawati Siswo wardoyo; Ai Sri Nurhayati; Kusnandar (LPPM Universitas Terbuka, 2020)
Learning Resources Center (LRC) in schools provides a wide selection of learning resources to support learning activities and encourage effective learning so as to achieve learning goals. LRC assistance has been provided from 2016 to 2019, so a research is needed to determine its utilization in schools.This research aims to determine the description of the utilization of ICT tools to support the learning process, as well as obstacles encountered, and recommendations for solution in use of ICT tools and content of LRC for learning in schools. Research uses evaluation research using CIPP (context, input, process and product). The samples are headmasters, teachers, and education staff in schools receiving PSB assistance from Data Center and Information Technology (Pusdatin) Ministry of Education and Culture Education Center in the 2016 to 2019 which is spread in various regions of Indonesi. Data collection using online questionnaires, interviews, limited observation, and documentation. The results showed that:1) the forms of utilizing PSB digital content in schools vary including: most teachers present in front of the class using projectors with the lecture method and some have integrated with other learning models, forms of use are used as independent learning resources for students both individually and in groups or on scheduled;2) in general the availability of inovative teachers is quite adequate, as many as 31% of schools have more than 5 teachers who are able to make independent digital learning materials and 53% of schools have less than 5 teachers who are able to make independent digital learning materials; 3)some recommendations in an effort to improve the quality of utilizing PSB digital content and PSB assistance tools, namely the need: increasing the availability of ICT infrastructure, improving the quality of HR management of PSB, increasing the quality of applications and quantity of PSB digital content, and improving the quality of policy support. Pusat Sumber Belajar (PSB) di sekolah menyediakan berbagai macam pilihan sumber belajar untuk mendukung kegiatan pembelajaran dan mendorong cara belajar yang efektif sehingga dapat mencapai tujuan pembelajaran. Bantuan PSB telah diberikan sejak tahun 2016 sampai dengan tahun 2019, sehingga perlu dilakukan kajian untuk mengetahui pemanfaatannya di sekolah. Penelitian ini bertujuan untuk mengetahui gambaran pemanfaatan bantuan perangkat TIK untuk menunjang proses pembelajaran, serta kendala yang dihadapi, dan rekomendasi solusi dalam pemanfaatan bantuan perangkat TIK dan konten PSB untuk pembelajaran di sekolah penerima bantuan PSB. Penelitian menggunakan penelitian evaluasi dengan menggunakan model CIPP (context, input, process dan product). Sampel adalah kepala sekolah, guru-guru dan tenaga kependidikan pada sekolah penerima bantuan perangkat PSB dari Pusdatin Kemendikbud Tahun 2016 s/d. Tahun 2019 yang tersebar di berbagai wilayah Indonesia. Pengumpulan data menggunakan kuesioner online, wawancara, observasi terbatas, dan dokumentasi. Hasil penelitian menunjukkan bahwa: 1) bentuk pemanfaatan bantuan konten digital PSB di sekolah beragam diantaranya: sebagian besar guru menyajikan di depan kelas menggunakan projector dengan metode ceramah dan ada yang sudah mengintegrasikan dengan model pembelajaran lainnya, bentuk pemanfaatan digunakan sebagai sumber belajar mandiri bagi siswa baik individu maupun kelompok atau secara terjadwal; 2)pada umumnya ketersediaan guru penggerak cukup memadai, sebanyak 31% sekolah memiliki lebih dari 5 orang guru yang mampu membuat bahan belajar digital mandiri dan 53% sekolah memiliki kurang dari 5 orang guru yang mampu membuat bahan belajar digital mandiri; 3) beberapa rekomendasi dalam upaya peningkatan kualitas pemanfaatan konten digital PSB dan perangkat bantuan PSB yaitu perlunya: peningkatan ketersediaan sarana prasarana TIK, peningkatan kualitas SDM pengelola PSB, peningkatan kualitas aplikasi dan kuantitas konten digital PSB, serta peningkatan kualitas dukungan kebijakan.